2002
DOI: 10.1097/00042560-200205010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced HIV Risk-Taking and Low HIV Incidence After Enrollment and Risk-Reduction Counseling in a Sexually Transmitted Disease Prevention Trial in Nairobi, Kenya

Abstract: There is an urgent need in sub-Saharan Africa to develop more effective methods of HIV prevention, including improved strategies of sexually transmitted infection (STI) prevention or an HIV vaccine. The efficacy of these strategies may be tested through clinical trials within cohorts at high risk for STI and HIV, such as female commercial sex workers. For ethical reasons, standard HIV prevention services, including access to free condoms, risk-reduction counseling, and STI therapy, will generally be offered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 11 publications
2
36
1
Order By: Relevance
“…33-35 71 75 Three of these targeted high-risk men, 35 71 75 another targeted women and truckers in Tanzania, 34 and the fifth offered risk-reduction counselling, STI treatment and condoms to sex workers in Kenya. 33 Again, only pre-post comparisons are presented, except in one non-randomised controlled trial (NRCT) among high-risk men in the Philippines. 75 Casual sex Six studies reported intervention impact on condom use with casual or non-regular sexual partners, with three documenting significant increases (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…33-35 71 75 Three of these targeted high-risk men, 35 71 75 another targeted women and truckers in Tanzania, 34 and the fifth offered risk-reduction counselling, STI treatment and condoms to sex workers in Kenya. 33 Again, only pre-post comparisons are presented, except in one non-randomised controlled trial (NRCT) among high-risk men in the Philippines. 75 Casual sex Six studies reported intervention impact on condom use with casual or non-regular sexual partners, with three documenting significant increases (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Programs to reduce risk behavior, such as those used during the rollout of ARV therapy or other HIV prevention campaigns in African countries, may serve as templates for risk behavior reduction strategies. 57,71 Because of the decreased ability of women to negotiate condom use in their relationships and the higher risk behaviors found in men throughout sub-Saharan Africa, programs specifically targeting men should also be considered. More immediately, risk behavior assessment must remain an important component of HIV vaccine clinical trials because it provides one of the only means of predicting changes in risk behavior that might occur at the population level in an actual mass vaccination campaign.…”
Section: Discussionmentioning
confidence: 99%
“…The groups in Nairobi (Fonck et al 2000;Kaul et al 2002Kaul et al , 2004 and Benin ⁄ Ghana (Labbe et al 2003) looked at the effect of PPT while the group in Cote d'Ivoire (Ghys et al 2001) tested regular screening for STIs. Neither the Cote d'Ivoire nor the Nairobi studies found a difference in HIV incidence between the arms.…”
Section: Treatment Of Bacterial Sexually Transmitted Infections Combimentioning
confidence: 99%
“…The RCT that did show an effect of presumptive treatment on STI rates detected this sample size problem and lengthened the enrolment period accordingly (Kaul et al 2002(Kaul et al , 2004.…”
Section: What Interventions Worked?mentioning
confidence: 99%